2015
DOI: 10.1007/s12035-015-9476-8
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Ketamine-Induced DNA Damage in Different Cell Types In Vivo

Abstract: The use of a combination of ketamine and xylazine is broadly used either for anesthesia or euthanasia in rodent animal models in research. However, the genotoxicity and mutagenic effects of these drugs are unknown. Therefore, the aim of this study was to evaluate these effects to help the understanding of elevated values in negative controls in genotoxic/mutagenic assays. Sixty CF-1 mice were divided into ten groups of six mice per group: negative control (saline), positive control (doxorubicin, 40 mg/kg), ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The negative findings could be due to the very low concentration of isoflurane to which the people were exposed. Employing comet assay and micronucleus test, Leffa et al demonstrated that anesthetic ketamine with and without xylazine could induce DNA damage in blood and brain cells of mice [66]. However, the dose of ketamine used in the experiment was not clinically relevant (140 mg/kg) [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative findings could be due to the very low concentration of isoflurane to which the people were exposed. Employing comet assay and micronucleus test, Leffa et al demonstrated that anesthetic ketamine with and without xylazine could induce DNA damage in blood and brain cells of mice [66]. However, the dose of ketamine used in the experiment was not clinically relevant (140 mg/kg) [66].…”
Section: Discussionmentioning
confidence: 99%
“…Employing comet assay and micronucleus test, Leffa et al demonstrated that anesthetic ketamine with and without xylazine could induce DNA damage in blood and brain cells of mice [66]. However, the dose of ketamine used in the experiment was not clinically relevant (140 mg/kg) [66]. In the current studies, we used a clinically relevant concentration of isoflurane (2 %) and found that the treatment with a clinically relevant concentration of isoflurane was able to induce DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…10E). Doxorubicin is commonly used as a positive control for comet assays because it is recognized for causing DNA damaging [59][60][61]. It is important to highlight that although significant DNA damage has been observed in the highest dose, the DNA damage in the cells (nucleoids) was predominantly minor (class 1 -data not shown), with only a few cells showing a large amount of damage (classes 2 and 3).…”
Section: In Vivo Assaysmentioning
confidence: 99%
“…Liu et al (2013) and Kristin et al (2003) add that a high dose of ketamine can influence genotoxicity in the blood cells and brain cortex of mice. DNA damage continually occurs 24 hours after the administration of anesthetic ketamine (Leffa et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Ketamine is a selective NMDA receptor inhibitor that works by decreasing calcium influx and brain injury (Zhang et al, 2007). Ketamine is sometimes combined with alpha-2 agonists, specifically xylazine (Leffa et al, 2015). Xylazine hydrochloride can act as an analgesic, sedative, and muscle relaxant (Gonca, 2015).…”
Section: Introductionmentioning
confidence: 99%